2008
DOI: 10.1086/593176
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variation in Group AStreptococcusPili and Association of Pilus Backbone Types with Lancefield T Serotypes

Abstract: We propose the use of a tee gene sequence typing, analogous to the emm gene typing, as a valuable molecular tool that could substitute for the serological T classification of GAS strains. From our sequence analysis and from recent epidemiological data, we estimate that a vaccine comprising a combination of 12 backbone variants would protect against > 90% of currently circulating strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
158
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(159 citation statements)
references
References 26 publications
1
158
0
Order By: Relevance
“…Recent studies have demonstrated that the homologue of Spy0125 (called Cpa) in a serotype M3 S. pyogenes strain is localized at the tip of pili (37). There is considerable diversity among the loci (known as FCT regions) encompassing pilus gene clusters in different strains of S. pyogenes, and the FCT-3 region of M3 S. pyogenes differs from the FCT-1 region of the M1 strain SF370 studied here (9,21). Nevertheless, by using LC-MS/MS analysis and the spy0128K 161 A mutant, Spy0125 was shown to be joined to the pilus shaft through an intermolecular isopeptide bond linking its C-terminal Thr 723 to the ε-amino group of Lys 161 in Spy0128.…”
Section: Discussionmentioning
confidence: 78%
“…Recent studies have demonstrated that the homologue of Spy0125 (called Cpa) in a serotype M3 S. pyogenes strain is localized at the tip of pili (37). There is considerable diversity among the loci (known as FCT regions) encompassing pilus gene clusters in different strains of S. pyogenes, and the FCT-3 region of M3 S. pyogenes differs from the FCT-1 region of the M1 strain SF370 studied here (9,21). Nevertheless, by using LC-MS/MS analysis and the spy0128K 161 A mutant, Spy0125 was shown to be joined to the pilus shaft through an intermolecular isopeptide bond linking its C-terminal Thr 723 to the ε-amino group of Lys 161 in Spy0128.…”
Section: Discussionmentioning
confidence: 78%
“…3D). The FCT locus is conserved in GAS strains of M-types 3, 5, 18, and 49 (FCT-3), but it shows variable gene content and poor sequence homology with FCT regions from other strains, such as M-type 1 GAS representing FCT-2 (15,46). srtC2 regulation was detectable in M-type 3 strain 003Sm, because our microarrays carry probes for the highly homologous srtC2 from M-type 18 GAS (spyM18_0129) (60), whereas regulation of the pilus structural genes was not detectable, since the microarrays contained probes specific to M-type 1 GAS.…”
Section: Resultsmentioning
confidence: 99%
“…The genes encoding pili of the pathogenic streptococci are found in discrete loci, termed PI. To date, three PI have been identified for S. agalactiae (512), two have been identified for S. pneumoniae (23), and nine have been identified for S. pyogenes (157), with the latter occurring within the Fn-binding, collagen-binding, T-antigen (FCT) region that forms part of the Lancefield T-serotyping system. While the exact composition varies, each PI comprises genes that encode LPxTz family proteins, which are linked to cell wall peptidoglycan precursors via sortase cleavage between T and z (see below).…”
Section: Pilimentioning
confidence: 99%